Emerging Market Local Currency Bond Yields and Foreign Holdings in the Post-Lehman Period : a Fortune or Misfortune? - Ebeke, Christian (IMF Working Papers; Working Paper, 2014)
The paper shows that foreign holdings of local currency government bonds in emerging market countries (EMs) have reduced bond yields but have somewhat increased yield volatility in the post-Lehman period. Econometric analyses conducted from a sample of 12 EMs demonstrate that these results are robust and causal. We use an identification strategy exploiting the geography-based measure of EMs financial remoteness vis-a-vis major offshore financial centers as an instrumental variable for the foreign holdings variable.The results also show that, in countries with weak fiscal and external positions, foreign holdings are greatly associated with increased yield volatility. A case study using Poland data elaborates on the cross country findings.